DETERMINAN RISIKO SISTEMATIS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK JAKARTA TAHUN 2003-2005 - Muljono, Muljono (Universitas Muhammadiyah Magelang, 2007)
This research represent the event study with the approach of case study of at Indonesia Stock Exchange using historical data of year 2003-2005. Sample will be taken by purposive sampling and company in Indonesia Stock Exchange. Analysis used in this research is multiple regression. The research was aimed at evaluating empirically the effects of five independent variable that included dividend pay out Ratio, leverage, earning, variability, liquidity and asset size on sistematic risk. The contribution of independent variables on dependent ones is indicated by determination coefficient test (R2 test). t test and F test  were applied to evaluate the hypothesis. In a simultan earning dividend pay out Ratio, leverage, earning, variability, liquidity and asset size having not significant influence to a sistematic risk (beta). The research is more influenced by the other variables exluded in the study.